Peran Strategis Industri Farmasi dan Apoteker dalam Menghadapi Pandemi di Masa Depan: Kesiapsiagaan Pandemi Global Pelajaran dari Covid-19 - Dewi, Rusmina Iswanti Kumala; U, Retry Atika; H, Daffa Islami; P, Veronika Deggi (Pharmaceutical Journal, 2025)
The COVID-19 pandemic has revealed significant weaknesses in the global health system,  including the lack of preparedness in the pharmaceutical sector to handle large-scale crises.  The pharmaceutical industry and pharmacists play a strategic role in ensuring drug  availability, vaccine production, distribution of medical supplies, and public education. This  article aims to systematically review the critical roles of the pharmacy sector during  pandemic responses and to evaluate necessary preparedness strategies for future health  emergencies. A literature review approach was used, focusing on international publications from the last decade. The findings highlight that cross-sector collaboration, digitalization of  pharmacy services, strengthening of supply chains, and emergency preparedness training for  pharmacists are key strategies in building global pandemic resilience. Additionally, inclusive  and evidence-based policies are essential to optimize the contribution of pharmacists and the  pharmaceutical industry in sustaining global health security. These insights form a strong  foundation for developing more resilient pharmacy systems in the future.